Towards Finite-Gap Integration of the Inozemtsev Model - Takemura, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The Inozemtsev model is considered to be a multivaluable generalization of Heun's equation. We review results on Heun's equation, the elliptic Calogero-Moser-Sutherland model and the Inozemtsev model, and discuss some approaches to the finite-gap integration for multivariable models.